Treasures of the Lake Zeway Churches and Monastery, South Central Ethiopia: Buruk Wolde Michael (Journal-of-Ethiopian-Church-Studies/የኢትዮጵያ-ቤተ-ክርስቲያን-ጥናት-መጽሔት-Live, 2013)
Lake Zeway is situated in one of the seven Rift Valley Lakes of Ethiopia. It is found at the northern tip of the lakes’ region.2 It is located at a distance of about 160kms south of Addis Ababa on the main road to the town of Shashemene.3 More specifically, it lies to the east of Zeway town, west of Asella town, south of Mount Bora, and north of Mount Alutto.4 The Lake is roughly heart-shaped5 covering an area of 434km2. 6Its average depth is 4m and it is the shallowest lake among the seven. In terms of its altitude, however, it is found at the highest elevation in the Rift Valley region located at a height of about 1846m above sea level